Efektivitas Inositol dan Metformin pada Sindrom Ovarium Polikistik (PCOS): Tinjauan Sistematis dari Uji Klinis Acak Terkontrol - Widya Puspita Sari; Daivan Febri Juan Setiya; Dinda Ashilah Putri Kusnan; Hani’a Fauza; Riyas Hasan Yazid; Meidy Zulvan Prabowo (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Polycystic ovary syndrome (PCOS) is a complex endocrine-metabolic disorder common in women of reproductive age, characterized by insulin resistance (IR), anovulation, and hyperandrogenism, often leading to infertility. Metformin is the first-line therapy used. However, inositol, especially myo-inositol (MI) and D-chiro-inositol (DCI), have shown promising therapeutic potential. Direct comparison and optimal efficacy of both still require a comprehensive review. Objective: This systematic review aims to evaluate the efficacy of inositol (as monotherapy or in combination) compared with metformin, placebo, or no intervention, in improving reproductive, hormonal, and metabolic outcomes in women with PCOS. Methods: Conducted according to PRISMA guidelines, a systematic literature search was conducted in Pubmed and Ebsco databases for randomized controlled trials (RCTs) published in the last 10 years. Studies evaluating inositol and/or metformin in women with PCOS and reporting reproductive, hormonal, or metabolic outcomes were included. Study selection and data extraction were performed independently by five reviewers. Results: Six randomized controlled trials (RCTs) were included in this review. Metformin consistently showed improvements in insulin resistance and androgen levels. Myo-inositol also demonstrated efficacy in improving metabolic and hormonal parameters, as well as reproductive outcomes, often with a better tolerability profile, especially as monotherapy. The combination of metformin and myo-inositol has shown potential improvements in some reproductive functions (such as live birth rate) compared to metformin alone in some studies. However, other studies have shown comparable or superior efficacy of myo-inositol monotherapy with fewer side effects. Adjuvant therapies such as dexamethasone or calcium/vitamin D have shown benefits in certain subpopulations. Conclusions: Both inositol (especially myo-inositol) and metformin have significant therapeutic roles in the management of PCOS. Metformin remains an important intervention for metabolic dysregulation and hyperandrogenism. Inositol appears to be an effective and often better tolerated alternative, with significant reproductive benefits. The choice of therapy should be individualized based on patient phenotype and treatment goals.